Toxicity of Thallium at Low Doses: A Review - Campanella, Beatrice (Int J Environ Res Public Health, 2019)
A mini review of the toxicity of Thallium (Tl) at low doses is herein presented. Thallium has severe toxicity. Although its acute biological effects have been widely investigated and are well known, its biological effects on human health and in cell cultures at low doses (<100 μg/L) due, for example, to Tl chronic exposure via consumption of contaminated water or foods, have often been overlooked or underestimated. Relatively few papers have been published on this topic and are herein reviewed to provide a focused scientific opinion in the light of current worldwide regulatory issues.